Social Life Cycle Assessment (S-LCA) of formal and informal waste collectors in decentralized waste to compost facility - Azad Ibn Ashraf; Eugene Mohareb; Maria Vahdati; Amith Khandakar (Cleaner Environmental Systems)
The global generation of municipal solid waste (MSW) is expected to increase by 70 % by 2050, reaching 3.4 billion metric tons. Despite the need for proper waste management, less than 20 % of waste is recycled, and waste continues to end up in landfills. Waste management is a significant problem in Bangladesh and other rapidly urbanizing nations, exacerbated by densely populated housing coupled with inadequate infrastructure. The utilization of informal waste collectors arises from the government's frequent inability to offer sufficient waste collection and disposal services. A large number of Dhaka's informal sector workers depend on collecting waste for a living. In this study, the social life cycle assessment (S-LCA) is applied to analyze the social implications of formal and informal waste collectors on the waste management process in Uttara, Dhaka. Working conditions, human rights, health and safety, and socio-economic repercussions are the four primary areas of focus for the S-LCA. For the assessment, an indicator score ranging from 2 (best performance) to −2 (poor performance) was used. The data revealed that informal workers scored 0 for fair salaries, but formal workers received 1, showing that formal workers adhere to higher standards. Both groups obtained an average score of −2 in the social security subcategory, which is much lower than anticipated. Formal workers scored −2 on health and safety, while informal workers scored −1, indicating serious inadequacies in both categories. These findings highlight the need for stronger legislation and support systems to enhance waste collectors' working conditions in Dhaka and other similar cities throughout the world, as well as the considerable socioeconomic challenges they confront.